2019
DOI: 10.1136/bmjinnov-2018-000324
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical ochronosis features in alkaptonuria: a cross-sectional study

Abstract: BackgroundAlkaptonuria (AKU) is present from birth, yet clinical effects are considered to appear later in life. Morbidity of AKU, considered irreversible, is secondary to ochronosis. Age of ochronosis onset is not clearly known. Nitisinone profoundly lowers homogentisic acid (HGA), the metabolic defect in AKU. Nitisinone also arrests ochronosis and slows progression of AKU. However, tyrosinaemia post-nitisinone has been associated with corneal keratopathy, rash and cognitive impairment in HT 1. The optimal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 33 publications
(18 reference statements)
2
38
0
2
Order By: Relevance
“…Thirty patients from different age-groups (from 16 years) were recruited and several outcomes evaluated: ochronosis on ear biopsy, visible ochronosis quantification in eyes and ears, MRI examination, deviation in gait, modified questionnaire Alkaptonuria Severity Score Index (qAKUSSI), circulating and urine HGA, biomarkers of inflammation, cartilage damage, bone and other tissue, and quality of life. 12 Pigmentation within ear biopsy was detected in a 20-year -old female, providing evidence that ochronosis can start in AKU patients before the age of 20 years. Eye ochronosis increased with age, and was first detected at age 22 years.…”
Section: Natural History Of Akumentioning
confidence: 89%
See 2 more Smart Citations
“…Thirty patients from different age-groups (from 16 years) were recruited and several outcomes evaluated: ochronosis on ear biopsy, visible ochronosis quantification in eyes and ears, MRI examination, deviation in gait, modified questionnaire Alkaptonuria Severity Score Index (qAKUSSI), circulating and urine HGA, biomarkers of inflammation, cartilage damage, bone and other tissue, and quality of life. 12 Pigmentation within ear biopsy was detected in a 20-year -old female, providing evidence that ochronosis can start in AKU patients before the age of 20 years. Eye ochronosis increased with age, and was first detected at age 22 years.…”
Section: Natural History Of Akumentioning
confidence: 89%
“…Interestingly, the inflammation biomarkers SAA and serum protein thiols increased with age, with no significant difference between AKU patients and controls. 12 Despite the lack of change in the spine and joints at ages <30 years (as MRI analysis showed), gait analysis was abnormal early on, since young patients had meandeviation profiles indicating that the gait had been affected at an early age. 12 Analysis also showed that quality of life appears to deteriorate seriously from the third decade.…”
Section: Natural History Of Akumentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest pigment in articular cartilage is seen in calcified cartilage cells at the junction between the calcified cartilage and subchondral bone . Similarly, OP is found in intervertebral discs and adjacent articular cartilage …”
Section: Detection Of Ochronosismentioning
confidence: 98%
“…However, direct detection of OP in vivo by Raman spectroscopy is possible. Such a technique has been validated in ex vivo tissue and is being adapted as an in vivo technique using ear cartilage and Achilles tendon, both tissues with little subcutaneous tissue …”
Section: Detection Of Ochronosismentioning
confidence: 99%